Factores de contexto socioeconómicos y educativos en estudiantes de nivel superior, sugerencias para una realidad actual - Gonzalez, Elvira Ivone (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2016)
The present research provides a comparative analysis of contextual factors and academic performance to see which of these factors can predict high or low academic level. Nonexperimental, cross country, formatted descriptive and analytical survey. Population of 45,161 university students and forced selection of a sample of 6,425 (14%) divided into two groups by performance: group under 1,233 (3%) and high group of 5,192 (11%). That predict variables at p <0.05 were: academic history (71.1%), hours spent at work in educational area (69%) eating habits (74%) forms of learning (79%) study habits (63%), the situation socioeconomic (58%) and poor educational facilities (60%). Recommendations to impact in terminal efficiency. That will allow young people insert prepared and responsible within the economically active society. The present research provides a comparative analysis of contextual factors and academic performance to see which of these factors can predict high or low academic level. Nonexperimental, cross country, formatted descriptive and analytical survey. Population of 45,161 university students and forced selection of a sample of 6,425 (14%) divided into two groups by performance: group under 1,233 (3%) and high group of 5,192 (11%). That predict variables at p <0.05 were: academic history (71.1%), hours spent at work in educational area (69%) eating habits (74%) forms of learning (79%) study habits (63%), the situation socioeconomic (58%) and poor educational facilities (60%). Recommendations to impact in terminal efficiency. That will allow young people insert prepared and responsible within the economically active society.